The Role of Social Media, the Attractiveness of Advertising, Prices and its Implications on Purchasing Decisions at Café Business in Polewali Mandar, Western Sulawesi - Andrian, Andrian; Wijayaningsih, Rini; Hasanuddin, Hasanuddin; Tutiek Yoganingsih (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine how prices, the allure of advertising, and the role of social media influence decisions about what to buy at a café in Polewali Mandar, Western Sulawesi. This study will employ a survey and quantitative method with a descriptive research approach and verification analysis because the goal is to provide an organized, factual account of the facts regarding the relationships between the variables under investigation. Survey research is the use of questionnaires as a tool for research in both small and large populations. SPSS 23 was used to analyze the data. According to the findings of this study, 86% of the Purchase Decision factors can be explained significantly by fluctuations in three independent variables: Social Media, Advertising Attractiveness, and Price. In contrast, 14% of the explanations came from sources other than the study's variables.